Oxygen Uptake Dynamics Conform to Acute Changes in Muscle Excitation and Total Hemoglobin Concentration during Constant-Work Rate Exercise - Marinari, Gabriele; Trama, Robin; Zagatto, Alessandro M. [UNESP]; Iannetta, Danilo; Murias, Juan M. (Wolters Kluwer, 2025)
Whether electromyography (EMG)-derived muscle excitation and near-infrared spectroscopy (NIRS)-derived total hemoglobin and myoglobin concentration (total[Hb + Mb]) are linked during cycling exercise is unknown. Purpose to investigate whether muscle excitation during constant-work rate (WR) cycling is connected with total[Hb + Mb] and interact with oxygen uptake (VO2) dynamics. Methods Experiment 1: ten participants performed a 21-min constant-WR (CWR) within the heavy-intensity domain (i.e., 75% of the difference between the gas exchange threshold and the maximal metabolic steady state), and a ramp-to-constant-WR (rCWR) to the same WR. CWR and rCWR were repeated twice and allocated in random order. Experiment 2: nine participants performed a double-constant-WR (dCWR) consisting of a 21-min exercise bout, a short 20-sec break, and a second bout of 21 min within the heavy domain. VO2, EMG root mean square (EMGRMS), total[Hb + Mb] and deoxygenated hemoglobin ([HHb]) were collected from the vastus lateralis. The EMGRMS/total[Hb + Mb] and EMGRMS/[HHb] ratios were computed. Results The EMGRMS was lower at min 1 and 7 and total[Hb + Mb] higher at min 1 during the rCWR compared to the CWR condition (all P < 0.05). EMGRMS displayed an overshoot at min 1 which was different from min 21 during the CWR condition (P < 0.05). EMGRMS did not display an overshoot following the 20 sec break during the dCWR condition. The EMGRMS/total[Hb + Mb] inverted ratio was not different from VO2 (%). The EMG magnitude of frequencies ranging from ∼30-to-90 Hz was initially higher and decreased over time (P < 0.05). Conclusions This study demonstrated that EMGRMS-derived muscle excitation can be reduced by exercise protocols that promote higher total[Hb + Mb]. Furthermore, the interaction between muscle excitation and total[Hb + Mb] matched with systemic VO2.
Keywords: DEOXYGENATED HEMOGLOBIN; MUSCLE EXCITATION; OXIDATIVE PHOSPHORYLATION; OXYGEN UPTAKE KINETICS; TOTAL HEMOGLOBIN CONCENTRATION